CO2 Hydrogenation on Metal-Organic Frameworks-Based Catalysts: A Mini Review - Zhang, Qian; Wang, Sen; Dong, Mei; Fan, Weibin (Frontiers in Chemistry, 2022)
Conversion of carbon dioxide (CO2) into value-added fuels and chemicals can not only reduce the emission amount of CO2 in the atmosphere and alleviate the greenhouse effect, but also realize the carbon recycling. Through hydrogenation with renewable hydrogen (H2), CO2 can be transformed into various hydrocarbons and oxygenates, including methanol, ethanol, methane and light olefins etc. Recently, metal-organic frameworks (MOFs) have attracted extensive attention in the fields of adsorption, gas separation and catalysis due to their high surface area, abundant metal sites and tunable metal-support interface interaction. In CO2 hydrogenation, MOFs are regarded as important supports or sacrificed precursors for preparation of high-efficient catalysts, which can uniformly disperse metal nanoparticles (NPs) and enhance the interaction between metal and support to prevent sintering and aggregation of active metal species. This work summarizes the recent process on hydrogenation of CO2 to methanol, methane and other C2+ products over various MOFs-based catalysts, and it will provide some dues for the design of MOFs materials in energy efficient conversion and utilization.